RAISA: Threat or Opportunity for Careers? A Study on Internship Students in Jabodetabek - Helen Helen; Ghisanie Azahra Alfyoni; Anastasia Bernessa Christianto; Sharon Jess; Kiky Dwi Hapsari Saraswati (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The development of Artificial Intelligence (AI), robots, and automation services (RAISA) show us the advancing technology, however, it also poses the potential of negative impacts that need to be addressed. One such impact is the takeover of career opportunities by RAISA, causing some college students to feel threatened about future prospects. This study analyzes the relationship between RAISA awareness and perceived future career opportunities (PFCO) among internship college students in universities within the Jabodetabek area. The researchers obtained 131 respondents from various universities, comprising 44 male and 87 female. The research data was processed using convenience sampling, utilizing RAISA awareness and PFCO questionnaires distributed online by Google Form. The data analysis revealed a Cronbach's alpha coefficient 0.923 for the RAISA Awareness and 0.819 for PFCO; Kolmogorov-Smirnov test p <0.05 for both indicating non-normal data distribution; and r (131) = +0.293, p <0.05 for the hypothesis test results using the Spearman's Correlation test. Then, it can be concluded that there is a positive and significant correlation between RAISA Awareness and PFCO among internship students in universities within the Jabodetabek area. AI, robot dan otomatisasi layanan (RAISA) menjadi bukti bahwa perkembangan teknologi semakin pesat, bahkan yang perlu diwaspadai adalah potensi dari dampak negatif yang diciptakan oleh kemajuan teknologi. Salah satunya adalah peluang karir yang makin banyak diambil alih oleh RAISA membuat sebagian mahasiswa merasa terancam akan masa depan berkarirnya. Studi ini menganalisis hubungan kesadaran terhadap RAISA dengan peluang karir masa depan pada mahasiswa magang di Jabodetabek. Peneliti mendapatkan 131 responden dari berbagai universitas di Jabodetabek dengan jenis kelamin laki-laki 44 orang dan jenis kelamin perempuan 87 orang. Data penelitian diolah menggunakan convenience sampling, menggunakan kuesioner RAISA awareness dan Perceived Future Career Opportunity (PFCO) yang disebar secara daring menggunakan Google Form. Hasil analisis data diketahui koefisien Cronbach’s Alpha yang diperoleh adalah 0.923 untuk variabel RAISA Awareness dan 0.819 untuk PFCO; Kolmogorov-Smirnov test p<0.05 untuk kedua variabel yang menunjukkan distribusi data tidak normal; dan r(129) = .29, p < .001 untuk hasil uji hipotesis menggunakan metode Spearman’s Correlation test. Sehingga dapat disimpulkan bahwa terdapat korelasi positif dan signifikan antara RAISA Awareness dengan PFCO pada mahasiswa magang di universitas Jabodetabek.